Reverse Objective Structured Clinical Examination (ROSCE) - Srivastava, Tripti K; Waghmare, Lalitbhushan (Canadian Medical Education Journal, 2018)
The authors propose a method "Reverse OSCE" which is built upon the principles of OSCE. It is a step forward to conventional OSCE wherein the role of tutor and student is reversed. Reverse OSCE as an assessment tool can assess the observational skill of a student along with knowledge and understanding of various procedural skills. It retains the obvious advantages of conventional OSCE in terms of objectivity, reproducibility, and easy recall along with the added benefit of versatility and ever broadening scope.